SYNTHETIC AND BIOLOGICAL UTILITY OF 2,3-DICHLORO-1,4-NAPHTHOQUINONE: A REVIEW - Maurya, Hardesh K. (International Journal of Research -GRANTHAALAYAH, 2019)
2,3-Dichloro-1,4-naphthoquinones (dichlone) have attracted considerable attention for the construction of biologically active tricyclic and tetracyclic 1,4-quinones and other derivatives. A diversified reaction of 2,3-dichloro-1,4-naphthoquinones such as cycloaddition, condensation, photo induced and nucleophilic substitution reactions with suitable nucleophiles viz. carbon, nitrogen, oxygen, sulfur, selenium etc have been explored. Various synthesized compounds have also explored for their biological activity such as antifungal, antibacterial, anticancer, antiplatlet, anti-inflamentry, anti-allergic and anti HIV. This review describes the chemistry and biological activity of compounds synthesized from 2,3-dichloro-1,4-naphthoquinones during the last three decades.